Influência do uso e ocupação da terra na qualidade da água subterrânea e sua adequação para consumo humano e uso na agricultura - Menezes, João Paulo Cunha de (2012)
Researches about water quality are essential for ensure it sustainable and safe use for human consumption, agricultural and industrial purpose. On this way, the aim of this work was to analyze groundwater quality in Alegre County, South of Espírito Santo